KEABSAHAN KEWENANGAN KURATOR DALAM MEMBUAT PERJANJIAN PERDAMAIAN SETELAH GAGALNYA PKPU DAN DEBITOR DINYATAKAN PAILIT (Contoh Kasus: Putusan No.486 PK/Pdt/2018) - Serlin Vanessa; F. X. Suyud Margono (Fakultas Hukum Universitas Tarumanagara, 2019)
Debt is something that is common in the business world. This loan must be approved in accordance with the period agreed upon by the parties. Loans given by Creditors to Debtors are carried out with approval.If within a predetermined time limit, the Debtor has not been able to repay the loan, the Debtor may request approval for Delaying Obligations of Debt Payment or PKPU. However, in this study, PKPU failed to do PT. Dewata Royal International was immediately bankrupt. After the bankruptcy was read out by the Court, Curator was appointed, Swandy Halim. Swandy Halim in carrying out his duties as a Curator has made a Peace Agreement with Rustandi Jusuf as the Managing Director of PT. Dewata Royal International. In UUK, PKPU approved the Curator's task was to bankrupt and not make a Peace Agreement, especially with the Bankrupt Debtor, because it was the Debtor with his Kreditors who made the Peace Agreement.The research method used by the author is normative legal research that focuses on the use of secondary data using descriptive analytical specifications. Then, the analysis of the data used by the author is qualitative research.In this study, conclusions were obtained about the Curator being able to make a Peace Agreement with a bankrupt Debtor as long as the above mentioned Peace Agreement is from bankrupt assets so as not to cause a loss to the bankrupt property. then, the Peace Agreement made by Curator Swandy Halim was then approved legally.